2017
DOI: 10.1124/jpet.117.240622
|View full text |Cite
|
Sign up to set email alerts
|

Arresting the Development of Addiction: The Role ofβ-Arrestin 2 in Drug Abuse

Abstract: The protein -arrestin (arr) 2 directly interacts with receptors and signaling pathways that mediate the behavioral effects of drugs of abuse, making it a prime candidate for therapeutic interventions. arr2 drives desensitization and internalization of G protein-coupled receptors, including dopamine, opioid, and cannabinoid receptors, and it can also trigger G protein-independent intracellular signaling.arr2 mediates several drug-induced behaviors, but the relationship is complex and dependent on the type of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 84 publications
1
31
0
Order By: Relevance
“…Our results showed that pro-inflammatory cytokines from RAW264.7 cells obviously increased at 6 h after treatment with LPS, which revealed that RAW264.7 could act as Kupffer cells when stimulated by LPS. It is well known that β-arrestin 2 is involved in various cell signaling pathways and plays a key role in the regulation of cell signaling[ 23 ]. For example, β-arrestin 2 acts as a scaffold protein and participates in the activation of JNK and ERK in the MAPK pathway[ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that pro-inflammatory cytokines from RAW264.7 cells obviously increased at 6 h after treatment with LPS, which revealed that RAW264.7 could act as Kupffer cells when stimulated by LPS. It is well known that β-arrestin 2 is involved in various cell signaling pathways and plays a key role in the regulation of cell signaling[ 23 ]. For example, β-arrestin 2 acts as a scaffold protein and participates in the activation of JNK and ERK in the MAPK pathway[ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beta-arrestin 2 (βarr2) plays a central role in the rewarding profiles of morphine, cocaine and alcohol [ 1 4 ]. In contrast, very little is known of the role of Beta-arrestin 1 (βarr1) in reward-motivated learning and behavior [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Opioid receptors are established drug targets for nonpeptide opioids such as morphine, fentanyl, or naloxone. These opioid receptor modulators are the most widely used analgesics in the clinic but their use is associated with severe drawbacks like tolerance, dependence, or respiratory depression, which were proposed to be linked to ligand and receptor bias towards arrestin recruitment [8][9][10] . Thus, a better understanding of opioid receptor signaling regulation and bias as well as new strategies to modulate opioid receptors with less adverse effects are not only timely but also urgently needed, especially considering the current opioid crisis.…”
mentioning
confidence: 99%